Relationship of genetic factors to the degree of Acne vulgaris as one of the predisposing factors in student Faculty of Medicine University of Muhammadiyah Malang - Dwi Nurwulan Pravitasari; Ratna Wulandari; Sri Adila Nurianiwati; M Yuliansyah Aldi Kurniawan; Raihan Fatihka Devi (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Acne vulgaris is a skin disease, a chronic inflammation that affects the poly sebaceous glands, especially on the face and neck. One of the endogenous causes that influence the occurrence of acne vulgaris is a genetic and hormonal predisposition. Family history of acne is one of the risk factors in family genetics associated with the onset of the disease, the difficulty of therapy, and the risk for relapse. This research aimed to explain the relationship between genetic factors to the degree of acne vulgaris as one of the predisposing factors. This research was observational analytic, using purposive sampling as the sampling method and collecting data using a cross-sectional questionnaire. Statistical analysis between variables shows that age was not related (p = 0,790), while gender was not related (p = 0,066), the father's genetic history was related (p = 0,001), and mother's genetic history was not related (p = 0,390). In conclusion, among the factors that were analyzed, the father's genetic history was the only one which has a relationship in aggravating the degree of acne vulgaris.